Chinese Teachers’ Perceptions on Perceived Teacher Support and Student Engagement - Shu, Zhan; Mottan, Kannamah; Chen, Haowei; Pang, Yao (Environment-Behaviour Proceedings Journal, 2024)
This qualitative study investigates the perceptions of teachers regarding methods to enhance students' perceived teacher support and engagement at a higher vocational college in Zhengzhou, China. The participants consisted of four instructors, each specializing in different subjects. Data were collected through semi-structured interviews. The findings reveal several effective strategies that participants use to enhance perceived teacher support and suggest ways to boost student engagement. These strategies offer valuable insights for improving both perceived teacher support and student engagement in the context of Chinese higher vocational education. The study also suggests directions for future research.